RESPON PENGGUNA WHATSAPP TERKAIT HOAKS KESEHATAN COVID-19 DI WHATSAPP GRUP KELUARGA - Putri Widiana (2022)
Indonesia is currently experiencing a coronavirus (Covid-19) pandemic. With the development of the pandemic, Indonesian people are trying to find information related to the corona virus. In reality, not all information circulating in social media is valid information. The Ministry of Communication and Information (Kominfo) said that social media is a place for spreading hoaxes. The WhatsApp application is one of the applications that are widely used by people in Indonesia today. The combination of ease of use and lack of literacy makes its users a WhatsApp medium that is widely used to spread hoaxes. The information that is widely spread on the WhatsApp application elicits user responses. The formulation of the research problem, namely the researcher wants to find out how the response given by WhatsApp users regarding Covid-19 Health Hoax information on Whatsapp Family Group. The purpose of this study is to find out how the response of Whatsapp users is related to the spread of hoaxes on Whatsapp Family Groups. The research theory used is the Stimulus Organism Response (S-O-R) Theory. The research approach used is a quantitative approach, with descriptive analysis research methods. Whatsapp user responses were measured based on Cognitive Response, Affective Response, and Conative Response. The results of the Crosstabulation Test (Crosstabulation) in this study indicate that there is a relationship between the demographic background of the user in the formation of a response. The demographic characteristics discussed in this study are Age, Gender, Education Level, and Type of Work. Recommendations Research that can be done is research related to the response of social media users to the spread of hoaxes that focuses on user behavior.